(untitled) (Eurasian Scientific Herald, 2022)
In job the results of study of material structure and enrichment of tests of ores of deposits Eshlik are given. As a result of the studies, recommended regimens for enrichment of ores were developed using a combination of a traditional collector and “CI” at a flow of 50% of the mixture of xantogenes and concentrates of higher quality were obtained